Contemplating employee retention through multidimensional assessment of turnover intentions - Tehmina Fiaz Qazi; Afia Khalid; Muhammad Shafique (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2015)
Several researches have studied the proposed relationships between the perception of organizational politics (POP), job insecurity, job embeddedness and turnover intentions. However, this study investigates a different explanation, by considering the moderating effects of static personality traits such as core self-evaluation (CSE) on Turnover intention (TI) when the employee, having varying levels of job embeddedness, (JE) is exposed to POP and job insecurity (JI). The worldwide increase in aspirations and provision of premium services in hospitality industry, especially in the five star category has led the customers to expect utmost superior service in every interaction. It needs skilled and customer oriented staff to maintain the set standards. In case of loss of such trained staff it results in faulty sales experience opportunity costs that may be detrimental to the reputation of the hotel, indicating turnover as a major concern in hospitality industry. There is a need to look through the lens of job embeddedness and CSE to understand actual and intended turnover, beyond the traditional job satisfaction prism to retain the trained staff. The data were obtained from employees of five-star hotels. Researcher- administered structured questionnaires were collected using multistage sampling method. 150 respondents were initially approached, 108 were duly filled in, constituting a response rate of 72%. It is found that POP and JI are positively related to TI. However the relationship is moderated by the CSE of employee that influence his experiences, behavior and intentions. Moreover the JE.is negatively related to TI and enhances the organization-employee fit and linkage. The results of the study suggest development of 'Retention Policy' that can be established through minimization of POP and enhancement in the JE of employees. Moreover, trust and transparency can be established by sharing information about the transparent reward policies, distinguishing high performing employees. This is particularly important in hospitality industry of Pakistan where the level of POP and injustice is particularly high. Making employees realize that they are not being mistreated/ manipulated is an important aspect to enhance their embeddedness. This can also tackle the problem of job insecurity. Furthermore, the hiring procedures of employees should make use of effective, objective and standard personality tests based on different dimensions, helping in acquiring the right caliber and traits of employees, ensuring their long term retention. The originality and value of the study lies in the application of a holistic person-oriented approach that inculcates the personality traits (CSE) of employees in determining the linkages between POP, JI, JE and TI. The empirical testing provides an important contribution to the hospitality management and marketing literature in Pakistan, providing not only a guideline for hiring and reward policies for employees who exhibit turnover intentions due to either POP and injustice in reward procedures or mismatch with the job requirements. It also highlights the need for hospitality management to devise mechanisms to increase the embeddedness (which was reportedly low/not recognized) to bear the fruits of such hiring policies.
Keywords: 330; turnover intentions; power & politics; job embeddedness; job insecurity; core self-evaluation